2021
DOI: 10.3389/fneur.2021.631343
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin-Platelet Clots in Acute Ischemic Stroke. Predictors and Clinical Significance in a Mechanical Thrombectomy Series

Abstract: Introduction: The histological composition of the clot influences its mechanical properties, affects the efficacy of endovascular treatment (EVT), and could determine the clinical outcome of patients with acute ischemic stroke (AIS). Insights into clot composition may guide therapeutic decision-making prior to EVT and facilitate revascularization therapies.Material and Methods: Consecutive patients with AIS recorded in a prospective single-center reperfusion registry from December 2015 to December 2019 and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…11 Furthermore, recent results from in vitro simulation of EVT also indicate that platelet thrombus content could impair EVT, notably by increasing thrombus stiffness and friction. 12,13 In line with other published series, 14,15 we report a different impact of thrombus platelet content according to the front-line strategy used, as this variable affected significantly the FPE rate in the CA but not in the SR group. In addition, and contrarily to others, who used a semi-quantitative technique 7 or in vitro model, 16 we did not find any difference in RBC content according to FPE status.…”
Section: Discussionsupporting
confidence: 87%
“…11 Furthermore, recent results from in vitro simulation of EVT also indicate that platelet thrombus content could impair EVT, notably by increasing thrombus stiffness and friction. 12,13 In line with other published series, 14,15 we report a different impact of thrombus platelet content according to the front-line strategy used, as this variable affected significantly the FPE rate in the CA but not in the SR group. In addition, and contrarily to others, who used a semi-quantitative technique 7 or in vitro model, 16 we did not find any difference in RBC content according to FPE status.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the nanoparticles developed in this work could be a valuable imaging tool, capable of predicting the effectiveness of rtPA based on the fibrin content of blood clots. On the other hand, recent studies have proven that the fibrin content in blood clots influences the success of recanalization in mechanical thrombectomy [ 8 ]. It was observed that the post-procedure serum levels of C-reactive protein were associated with the fibrin content in clots, and therefore could be used to indirectly predict fibrin-rich clots in ischemic stroke patients [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent studies have proven that the fibrin content in blood clots influences the success of recanalization in mechanical thrombectomy [ 8 ]. It was observed that the post-procedure serum levels of C-reactive protein were associated with the fibrin content in clots, and therefore could be used to indirectly predict fibrin-rich clots in ischemic stroke patients [ 8 ]. Instead, the nanoparticles developed in this work could be used to directly visualize and identify fibrin-rich clots before submitting the patient to recanalization therapy, thus representing a potentially useful tool in both mechanical and pharmaceutical recanalization therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations